Sappington Bridge: An Opportunity for Strengthening Research and Demolition Training - J. Baird (International Society of Explosives Engineers, 2003)
The Sappington Bridge, a steel arch span bridge constructed in 1904 over the Meramec River, was demolished due to its advanced state of deterioration. The demolition was a project to benefit Crawford County, Missouri, the U.S. Army, the Missouri Department of Transportation, and the University of Missouri – Rolla (UMR) was conducted jointly by the UMR Rock Mechanics and Explosives Research Center (RMERC) and the UMR Center for Infrastructure Engineering Studies (CIES). By arrangement with Crawford County, a 55-foot span of the old bridge was brought to the University Structures Laboratory in Rolla, while the longer, 200-foot span of the bridge was demolished using preburning and explosives. Originally, the longer span was to be blown up by C Company of the 5th Engineer Battalion (from Ft. Leonard Wood, Missouri) under the supervision of personnel from UMR. Unfortunately, permission for the operation from the Department of the Army could not be obtained in time to meet permitting requirements for the demolition. Therefore, a commercial demolition contractor was employed to perform the demolition, and to remove the scrap.